2021
DOI: 10.1155/2021/8046680
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Virulence Genes and Antimicrobial Resistance of E. coli O157:H7 Isolated from the Beef Carcass of Bahir Dar City, Ethiopia

Abstract: E. coli O157:H7 is one of the most virulent foodborne pathogens. The aim of this study was to isolate E. coli O157:H7, determine virulence genes carried by the organism, and assess the antimicrobial susceptibility pattern of the isolates from beef carcass samples at Bahir Dar city. Swab samples (n = 280) were collected from the carcass of cattle slaughtered at the abattoir and processed using sorbitol MacConkey agar supplemented with cefixime telluride and confirmed with latex agglutination test. A polymerase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Using previously reported occurrence of E. coli O157:H7 (8.9%) in Bahir Dar city, municipal abattoir (Habtamu et al, 2021 ), 1.96 Zα /2 value at a confidence level of 95%, 5% required absolute precision, the estimated sample size was 124. The sample size of butcher shop samples was equal to the respective carcass received from each municipal abattoir.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using previously reported occurrence of E. coli O157:H7 (8.9%) in Bahir Dar city, municipal abattoir (Habtamu et al, 2021 ), 1.96 Zα /2 value at a confidence level of 95%, 5% required absolute precision, the estimated sample size was 124. The sample size of butcher shop samples was equal to the respective carcass received from each municipal abattoir.…”
Section: Methodsmentioning
confidence: 99%
“…In Ethiopia, a number of studies have been conducted about the occurrence and antibiograms of E. coli O157:H7 isolates from food of animal origin, animal surfaces, and samples taken from slaughterhouses, retail shops, and restaurants (Abebe et al, 2023 ; Aklilu et al, 2017 , 2022 ; Ashenafi et al, 2017 ; Biruhtesfa et al, 2017 ; Eshetu et al, 2021 ; Habtamu et al, 2021 ; Melaku et al, 2013 ; Mengistu & Eyob, 2020 ; Nega et al, 2021 ; Rosa et al, 2017 ; Shimelis et al, 2017 ; Tizeta et al, 2014 ). However, most of those studies focused on the prevalence and antimicrobial susceptibility of E. coli O157:H7 , and some of them focused on identifying the potential microbial contamination source of E. coli O157:H7 along the chain of meat production process starting from slaughtering up to ready for human consumption and there was no previous study done on the occurrence and antibiograms of E. coli O157:H7 , and the potential contamination points at abattoirs and butcher shops in Awi Zone.…”
Section: Introductionmentioning
confidence: 99%
“…Although data regarding the contamination of carcasses by the DEC in abattoirs are scarce in Ethiopia in general and in northwest Ethiopia in particular, there are few reports on the magnitude, microbial loads and E. coli O157:H7 contamination of meat. Some of the reports were 4.9% at the Mojo export abattoir [20], 9.3% at the Jima municipal abattoir [21], 8.1% at the Bishoftu slaughterhouse [22] and 8.9% at the Bahir Dar city beef carcass [23]. In the northwest part of Ethiopia, though there are some studies that reported the detection of DEC isolates and antimicrobial resistance from apparently healthy slaughtered animals, butcher shops, and butchers, we believe that there is limited evidence on the detection of DEC isolates, the virulence genes, and antibiogram pro le from one health perspective [23].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the reports were 4.9% at the Mojo export abattoir [20], 9.3% at the Jima municipal abattoir [21], 8.1% at the Bishoftu slaughterhouse [22] and 8.9% at the Bahir Dar city beef carcass [23]. In the northwest part of Ethiopia, though there are some studies that reported the detection of DEC isolates and antimicrobial resistance from apparently healthy slaughtered animals, butcher shops, and butchers, we believe that there is limited evidence on the detection of DEC isolates, the virulence genes, and antibiogram pro le from one health perspective [23]. Thus, the study was gird with the aim to isolate, detect and assess antibiogram pro les of DEC from slaughtered cattle (feces and carcass), slaughter environment (abattoir water and e uent) and equipment (knives), and hand swabs from abattoir workers in Gondar ELFORA and Bahir Dar municipal abattoirs, northwest Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…Given the generally poorer hygienic conditions and disease prevention capacity in rural areas in low-income countries, these risks may be accentuated in such settings. However, data on the occurrence of different E. coli pathotypes in low-income countries is sparse [ 17 , 18 , 19 , 20 ]. Here, we provide such data from diarrheic calves in a district in Ethiopia, the most livestock-rich country in Africa [ 21 ].…”
Section: Introductionmentioning
confidence: 99%